Pengaruh Profitabilitas dan Leverage terhadap Kebijakan Dividen Perusahaan Sektor Kesehatan yang Terdaftar di Bursa Efek Indonesia (BEI) - Dhia Sellya Mufida Susilo; Isni Andriana; Kemas Muhammad Husni Thamrin (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2023)
This study aims to determine and analyze the effect of profitability and leverage on the dividend policy of health sector companies listed on the Indonesia Stock Exchange (IDX). This research is quantitative correlation research. The type of data used is quantitative data which is panel data. Data collection techniques using the documentation method. The population of this study consisted of 23 companies. The sample selection used a purposive sampling technique so that the research sample was 12 health sector companies listed on the Indonesia Stock Exchange (IDX) for the period 2017 – 2020. The data analysis technique used descriptive statistical analysis and panel data regression with the Eviews program. The results of this study are profitability and leverage have a positive and significant impact on the dividend policy of health sector companies listed on the Indonesia Stock Exchange (IDX).